Knowledge and attitude of human monkeypox among university students and staff in Tehran, Iran - Alimohamadi, Yousef; Sepandi, Mojtaba; Marhamati, Tahereh (Frontiers in Public Health, 2025)
BackgroundEffective control of any disease, including Monkey pox (mpox), is highly dependent on public knowledge and adherence to preventive measures. This cross-sectional study was conducted with the aim of investigating the knowledge of students and staff of Baqiyatallah University about the origin of mpox and its symptoms, transmission, prevention, and management.MethodsIn the current cross-sectional study, the data was collected from Aug 5, 2024 to Sep 5, 2024. The target population consisted of students, teachers, and the staff of Baqiyatallah University, aged 18 or above. Multiple Logistic regressions were employed to assess the association between participants’ overall knowledge about human mpox as well as their attitude and their demographic data. Data was analyzed using IBM SPSS statistics version 23.0 (IBM Corp., Armonk, NY, USA) and subsequently coded and labeled. The statistical significance level was set at 5%.ResultsThe overall mean score of participants’ knowledge and attitude was 6.37 ± 2.20 and 4.24 ± 1.71, respectively. Based on Bloom’s cut-off points, 458 (84.3%), 78 (14.4%), and 7 (1.3%) of the participants had low, moderate, and high knowledge levels, respectively and, 279 (51.4%), 221 (40.7%), and 43 (7.9%) of the participants had low, moderate, and high attitude levels, respectively. Logistic regression analysis showed that job status(OR: 9.6, 95% CI: 1.3–66.4), major(OR: 4.3, 95% CI: 1.3–14), and higher educational level (OR: 7.6, 95% CI: 1.03–61.8), was significantly associated with participants’ knowledge about mpox.ConclusionThis study showed that university students and staff in Iran do not have enough knowledge about mpox, including its symptoms, preventive measures, and treatment, with a good understanding of local and international health authorities in the control of emerging mpox. People with higher education tend to have better knowledge, which indicates that access to reliable information sources is necessary to acquire accurate knowledge.